2008
DOI: 10.1007/s00256-008-0486-8
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of the sacral plexus and piriformis muscles

Abstract: The S1 nerve roots course above the piriformis muscle in more than 99% of patients. The S2 roots traverse the piriformis muscle in 75% of patients. The S3 nerve roots traverse the piriformis muscle in 97% of patients. Piriformis muscle size asymmetry is common, with muscle asymmetry of up to 8 mm identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 14 publications
0
23
0
3
Order By: Relevance
“…The correct treatment can be started following a thorough investigation into the cause of symptoms. Apart from MR neurography, pelvis MRI remains unable to define a criterion for diagnosis, since asymmetrical size of the piriformis muscle is common in normal people (25). Electromyography is another test for diagnosis, but nerve conduction results reported in the literature were not conclusive and their methods were very controversial.…”
Section: Akdemir Ozisik P Et Al: Ct-guided Piriformis Muscle Injectionmentioning
confidence: 99%
“…The correct treatment can be started following a thorough investigation into the cause of symptoms. Apart from MR neurography, pelvis MRI remains unable to define a criterion for diagnosis, since asymmetrical size of the piriformis muscle is common in normal people (25). Electromyography is another test for diagnosis, but nerve conduction results reported in the literature were not conclusive and their methods were very controversial.…”
Section: Akdemir Ozisik P Et Al: Ct-guided Piriformis Muscle Injectionmentioning
confidence: 99%
“…Bu bulgular, ileri evre hastalığa işaret eder ve kaslardaki hasar geri dönüşümsüzdür. [4] ALT EKSTREMİTE TUZAK NÖROPATİLERİ Pelvis ve kalça bölgelerinde en çok etkilenen sinirler lumbosakral pleksus, femoral sinir, lateral kutanöz sinir, obturator sinir, siyatik sinir (piriformis sendromu) ve gluteal sinirdir. Alt ekstremitede en sık bası altında kalan sinirler ise, ana peroneal sinir ve dalları, tibial sinir ve dalları ile sural sinirdir.…”
Section: İndirekt Bulgularunclassified
“…Kas asimetrileri, 4 mm ve üzerinde anlamlı bulunmuştur. [4] Aksesuvar piriformis kasları izlenebilir.…”
Section: Derin Peroneal Sinir (şEkil 11)unclassified
“…In contrast to this, Sayson 37 and Barton 28 found pre-operative MRI failed to diagnose atypical anatomy that was found intra-operatively. Further undermining the significance of positive findings on MRI reports, is the study by Russell et al 25 who examined the piriformis muscle and sciatic nerves in 100 patients who did not have symptoms of PS. Findings showed that almost one in five subjects had greater than 3mm of asymmetry in the size of their piriformis muscles, with a maximum of 8mm, and the percent of nerve roots that traversed the muscle was < 1% at S1, but 95% and 97% at S2 and S3, respectively.…”
Section: Diagnostic Imagingmentioning
confidence: 99%
“…24 It is innervated by a nerve that originates in the S1 and S2 segments. However, considerable variation exists, with the S2 and S3 nerve roots said to pass through the muscle in some symptomatic patients, 13 and in a large percentage of asymptomatic live controls 25 and cadavers. 26,27 The muscle's main functions are 1) to externally rotate the thigh and 2) to abduct the thigh when the hip is flexed.…”
Section: Clinical Anatomymentioning
confidence: 99%